Synthesis and Characterization of Poly(hydroxy)urethane from Polyols for Beech (Fagus sylvatica) Wood Impregnation - Vera Junita Sitanggang; Nyoman Jaya Wistara; Philippe Gérardin (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
A non-isocyanate route of polyurethane synthesis based on polyol (xylitol, sorbitol, glycerol, and PG3), alkyl carbonate (DMC and DEC), and diamine (HMDA, EDA, and DETA) was conducted for wood impregnation through in-site polymerization. The structure and mass average molecular weight (Mw) of the polyurethanes were analyzed using FTIR, NMR, and SEC. According to the results, polyurethane synthesis by a two-pot method in water brought cyclic carbonate degradation. The distribution of Mw of the polyurethanes showed that the most satisfying polymer (4380 g/mol) was prepared without solvent. Polyurethanes synthesized in methanol have a higher Mw than that in distilled water. In the same solvent, the use of HMDA resulted in a polymer with higher Mw than that of EDA. One-step wood impregnation in a solvent gave unsatisfactory WPG (12.59–19.71%) and LC (50.36–62.80%). However, one-step impregnation without solvent gave a higher WPG (78.39–87.63%) and a lower LC (19.11–21.25%). It is not feasible to be applied industrially. The two-step impregnation gave WPG (14.89-30.73%) and LC (42.22–56.52%). Wood impregnation using methanol or ethanol as the solvent was more recommended than using an aqueous solution. However, the resistance against leaching needs improvement. Keywords: Alkyl carbonate, diamine, polyol, polyurethane, wood impregnation